2015
DOI: 10.3390/md13020697
|View full text |Cite
|
Sign up to set email alerts
|

Sulphated Polysaccharides from Ulva clathrata and Cladosiphon okamuranus Seaweeds both Inhibit Viral Attachment/Entry and Cell-Cell Fusion, in NDV Infection

Abstract: Sulphated polysaccharides (SP) extracted from seaweeds have antiviral properties and are much less cytotoxic than conventional drugs, but little is known about their mode of action. Combination antiviral chemotherapy may offer advantages over single agent therapy, increasing efficiency, potency and delaying the emergence of resistant virus. The paramyxoviridae family includes pathogens causing morbidity and mortality worldwide in humans and animals, such as the Newcastle Disease Virus (NDV) in poultry. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 55 publications
2
79
1
Order By: Relevance
“…Fucoidans exert their antiviral activities by blocking the interaction of viruses with the cells, thus inhibiting viral-induced syncytium formation [82]. This property led to attachment of fucoidan to the F0 protein resulting in a great antiviral potency of fucoidan, e.g., higher than the antiviral drug ribavirin [83]. Last but not least, fucoidans also display bioactivity on the immune system at cellular and humoral level by increasing macrophage phagocytosis [84].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Fucoidans exert their antiviral activities by blocking the interaction of viruses with the cells, thus inhibiting viral-induced syncytium formation [82]. This property led to attachment of fucoidan to the F0 protein resulting in a great antiviral potency of fucoidan, e.g., higher than the antiviral drug ribavirin [83]. Last but not least, fucoidans also display bioactivity on the immune system at cellular and humoral level by increasing macrophage phagocytosis [84].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…On the other hand, Ulvans are found in green seaweeds of the order Ulvales, and some species of the genus Ulva sp. have shown antiviral activities [18,19].…”
mentioning
confidence: 99%
“…Therefore, this study demonstrated apparent anti-bacterial and cutaneous wound healing effects of fucoidan. Fucoidan is known for its anti-bacterial, anti-viral, immunostimulatory, and healing stimulating effects [2][3][4][5][6][7][8][9][10][11]. In a previous study, fucoidan inhibited the growth of Staphylococcus aureus and Escherichia coli [5].…”
Section: Discussionmentioning
confidence: 99%
“…tangleweed (Lami-naria japonica), wakame (Undaria pinnati da Sporophyll) and limu moui (Cladosiphon okamuranus) [1]. Fucoidan is known for its anti-bacterial, anti-viral, immunostimulatory, and healing stimulating effects [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%